Inventarisasi Gulma Pada Pertanaman Kacang Tanah (Arachis hypogaea L.) Di Kabupaten Ogan Komering Ilir Sumatera Selatan - Syamsul Rizal; Yunita Panca Putri; Ima Santika (Indobiosains, 2023)
Research on the inventory of weeds on peanuts crops (Arachis hypogaea L.) in the village of Tanjung Merindu sub district Tanjung Lubuk Ogan Komering Ilir, has been carried out paper March to April 2019. This study aims to determine what kind of weed found in peanut crop (Arachis hypogaea L.) in the village of Tanjung Merindu sub district Tanjung Lubuk Ogan Komering Ilir. The research used descriptive survey method with exploring technique. Weeds that can be made key determination, identification, and made herbarium. Result of research got 2 Division, 3 Class, 7 Ordo, 7 Familia, 9 Genus, and 9 Species weeds are: Cyperus rotundus L., Axonopus compressus Swartz., Imperata cylindrica L., Brachiaria mutica Forsk., Euphorbia hirta L., Ageratum conyzoides L., Mimosa pudica Duchass., Cleome rutidosperma Backer., dan Neprholepis exaltata Schott.Â Keywords: Inventory, Weeds, Peanuts.Â